Fc-gamma receptors are not involved in cartilage damage during experimental osteoarthritis. Issue 7 (July 2015) - Stock, M.; Distler, A.; Distler, J.; Beyer, C.; Ruiz-Heiland, G.; Ipseiz, N.; Seeling, M.; Krönke, G.; Nimmerjahn, F.; Schett, G.
Summary: Objective: Fc-gamma receptors (FcγRs) have been shown to play a crucial role in cartilage degradation during experimental arthritis. Although most of their effect on cartilage degradation has been attributed to their potential to promote inflammation in the presence of immunoglobulins, activating FcγRs promote cartilage degeneration in antigen-induced arthritis (AIA) independently of the level of inflammation. This prompted us to investigate, whether FcγRs may also play a role in osteoarthritis (OA)-related cartilage degradation. Methods: FcγR expression was measured by RT-PCR and FACS in murine cartilage tissue and chondrocytes. Experimental OA was induced by destabilisation of the medial meniscus (DMM) in WT mice and animals lacking either activating (Fc receptor γ-chain-deficient) or inhibitory (FcγRIIB-deficient) FcγRs. Cartilage damage was investigated histologically 8 weeks post-surgery by assessing proteoglycan loss and structural damage according to OARSI recommendations. Osteophyte size was measured to investigate alterations in bone turnover. Results: Expression analyses revealed significant levels for all four types of murine FcγRs in mouse chondrocytes and cartilage tissue from newborn and 8-week-old mice. Surprisingly, yet, ablation of either activating or inhibitory FcγRs did not affect cartilage damage or bone turnover during DMM-induced OA in mice. Conclusion: While FcγRs appear to have a crucial role in cartilage degradation during inflammatory arthritis our data indicate that FcγRs do not influence cartilage destruction in experimental OA. This indicates that a certain threshold of inflammation is a prerequisite for FcγR-induced cartilage destruction in arthritis.